2016
DOI: 10.1371/journal.pone.0147413
|View full text |Cite
|
Sign up to set email alerts
|

Population Size Estimation of Men Who Have Sex with Men in Tbilisi, Georgia; Multiple Methods and Triangulation of Findings

Abstract: IntroductionAn accurate estimation of the population size of men who have sex with men (MSM) is critical to the success of HIV program planning and to monitoring of the response to epidemic as a whole, but is quite often missing. In this study, our aim was to estimate the population size of MSM in Tbilisi, Georgia and compare it with other estimates in the region.MethodsIn the absence of a gold standard for estimating the population size of MSM, this study reports a range of methods, including network scale-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…This finding should be interpreted with caution given the subjectiveness of the method and its succeptibility to several biases and unmeasured influences which may lead to under- or over- estimations. Indeed, previous studies applying multiple PSE methods including WOTC, the WOTC method have shown both under-estimation (e.g., MSM in Nairobi in Kenya, FSW in Yangon and Mandalay in Myanmar [ 14 , 25 ]), or over-estimation (e.g., MSM in Georgia [ 9 ]) of the population size in compare with other size estimation methods. Considering the highly criminalized and stigmatised nature of sex work in Iran [ 6 ], FSW might have exaggerated the estimates in an effort to normalize their sex work practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding should be interpreted with caution given the subjectiveness of the method and its succeptibility to several biases and unmeasured influences which may lead to under- or over- estimations. Indeed, previous studies applying multiple PSE methods including WOTC, the WOTC method have shown both under-estimation (e.g., MSM in Nairobi in Kenya, FSW in Yangon and Mandalay in Myanmar [ 14 , 25 ]), or over-estimation (e.g., MSM in Georgia [ 9 ]) of the population size in compare with other size estimation methods. Considering the highly criminalized and stigmatised nature of sex work in Iran [ 6 ], FSW might have exaggerated the estimates in an effort to normalize their sex work practice.…”
Section: Discussionmentioning
confidence: 99%
“…We also integrated the service and unique object multiplier methods [ 3 , 9 ] into the 2015 IBBS surveys to estimate the number of FSW in the 13 cities. Estimation of the total size of the population using multiplier methods relies on two overlapping but independent sources of information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FSW and MSM together accounted for 9.3% of Yunnan's estimated prevalent cases in 2017. This is lower than the share of these key groups in past Spectrum-STI estimates 35,36,40 , and in HIV incidence estimates [41][42][43][44] , which reflects that both the estimated prevalence of syphilis in FSW and Yunnan's key population size estimates are lower than in other countries 7,9,45,46 . The size estimate of FSW was based on self-identified sex workers; and almost certainly is an under-estimate of the total number of women who engage in transactional sex work.…”
Section: Discussionmentioning
confidence: 81%
“…Inference is made based on rearranging the simple identity p t = M t / N to solve for N . Although the multiplier method is only defined for a single trait, in recent applications, one sees a trend in using data on multiple traits to infer the size of the same population (Sulaberidze et al ; Johnston et al ; Okal et al ; Raymond et al ) in hopes of “strength in numbers.” Often this happens when the marginal counts for several traits are already available to a public health agency, so that resources are spent only to gather data on trait proportions within the target population via a single sample survey. In the cited studies, this collection of data is analysed on a trait‐by‐trait basis without aggregating the information into one single estimate; hence, we cannot be certain of the amount of information truly gained.…”
Section: Introductionmentioning
confidence: 99%